Analysis of Service Performance at Kotabumi Lampung Train Station using the Kano Method - Oktavia, Amelia; Aryani, Marnida; Prayogi, Galih Rio; Michael, Michael (CIVED, 2024)
The Railway Station is an essential thing in the operation of the train. Passenger trains will raise and lower passengers, both the initial destination of passengers and transit. Kotabumi Railway Station is a station whose activities are to raise and lower passengers; in this case, the train station must have excellent and effective service performance for passengers. So, it is necessary to research the level of passenger satisfaction with the benchmarks for the service performance of train stations regulated in the Minister of Transportation Regulation No. 63 of 2019 concerning Minimum Service Standards. These benchmarks are then submitted as questions to the passengers, which are then processed using the kano method to determine the level of passenger needs and satisfaction. The kano method on the level of passenger satisfaction at the Kotabumi Railway Station results in that 19 attributes are one-dimensional where service performance if fulfilled, will experience the pleasure that is balanced with the existing version, and six characteristics of satisfaction levels are in the indifferent category, namely service performance must remain maintained. Furthermore, the highest CS and DS values ​​were obtained for information on train arrivals and station operating schedules. If this service performance is fulfilled, the passenger satisfaction level is 0.77. If the service performance is not fulfilled, passenger disappointment is at -0.82, so this attribute must be a top priority.